Causal modeling and use in health psychology - bechka, azzeddine (Journal of Social Sciences and Humanities, 2021)
Health has recently been associated with the general absence of diseases from the body, whether organic or mental, but beyond to provide reasons for well-being and wellness at various stages of life and at different ages. However, attaining this optimal health requires an environment free of pathogens on the one hand and specialists capable of accurately diagnosing the causes of the disease in order to develop effective intervention mechanisms. This article presents a theoretical view of the latest modern methods adopted by health psychology, which is causal modeling, which is very important and envisages many goals aimed at promoting the health of the individual and society.